A house for everyone. Propaganda use of housing in NO-DO during the Franco dictatorship (1939-1975) - Fernández, Antonio Raúl; Hellín, Pedro; Trindade, Eneus [UNESP] (Universidad Complutense de Madrid (UCM), 2020)
This article analyzes the use of housing by the Dictatorship of Franco (1939-1975) through the Documentary Newsletter (NO-DO). A total of seventy-five documents whose main theme is housing were analyzed. Categorization and content analysis were the methods used. It is analyzed if the house functioned as a propaganda element for the political and social legitimation of the Franco regime. From this point, we suggest a reflection on the current characteristics of the Spanish real estate sector and its possible relationship with the imaginary and francoist policies on housing.
Una casa para todos. Uso propagandístico de la vivienda en NO-DO durante la dictadura de Franco (1939-1975)
Keywords: Dictatorship of Franco; Housing; NO-DO; Spain